Far from 'mission accomplished': time to re-energise tobacco control in Australia - Paul Grogan; Emily Banks (Sax Institute, 2020)
Smoking prevalence in Australia has decreased by 75% over the past 40 years. A major reduction in disease burden attributed to smoking has occurred in parallel, adjusted for the time lag between tobacco harms and disease occurrence. Yet, paradoxically, governments have seldom invested in tobacco control measures that require a financial outlay, such as social marketing, at required levels for optimal outcomes. The percentage of disease burden caused by smoking in Australia (9.3%) remains higher than that of any other preventable risk factor and the social costs are estimated at $136.9 billion annually. Tobacco control is rightly seen as an Australian public health success story. However, with up to two in three of Australia's 2.5 million current smokers at risk of dying prematurely from a smoking-related disease, much more needs to be done. In this paper, we explore a brief history of tobacco control in relation to policy reform and recent evidence, and outline the case for re-energising tobacco control at a time when public health has gained new political and social currency.